HYPERBOLIC EXPRESSIONS AMONG NEWLY MOTHERS IN TEXT-BASED VIRTUAL COMMUNICATION - Dian Budiarti; Agry Pramita; Irdan Hildansyah (Linguistik Indonesia, 2024)
The present study examined the use of hyperbolic expressions in a text-based virtual communication context, specifically in an Indonesian newly mothers’ online chat room. The study employed a descriptive qualitative method to analyze 60 utterances containing hyperbolic expressions taken from the Mom Sharing WhatsApp group. Simak and catat methods were implemented to observe and take notes on the hyperbolic expressions used by the mothers identified based on McCarthy & Carter’s (2004) characterization. The collected data were then categorized into 7 forms of hyperbole proposed by Claridge (2010), and the possible functions behind the use of this figurative language were analyzed qualitatively based on the overall contexts. Results reveal that 6 forms of hyperbole were used in the chat room, namely single-word hyperbole, phrasal hyperbole, clausal hyperbole, numerical hyperbole, the role of superlative, and comparison. Furthermore, the expressions were found to serve various functions, namely to express emotions, to concretize the message and evoke imagination, to create humour, and to establish group identity. These findings contribute to the ongoing discourse on the use of hyperbole in everyday communication.